2017
DOI: 10.1038/srep43940
|View full text |Cite
|
Sign up to set email alerts
|

Anordrin Eliminates Tamoxifen Side Effects without Changing Its Antitumor Activity

Abstract: Tamoxifen is administered for estrogen receptor positive (ER+) breast cancers, but it can induce uterine endometrial cancer and non-alcoholic fatty liver disease (NAFLD). Importantly, ten years of tamoxifen treatment has greater protective effect against ER+ breast cancer than five years of such treatment. Tamoxifen was also approved by the FDA as a chemopreventive agent for those deemed at high risk for the development of breast cancer. The side effects are of substantial concern because of these extended met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(59 reference statements)
2
5
0
1
Order By: Relevance
“…More recently, a similar strategy has been investigated by targeting plasma membrane ERs. More specifically, Gu et al showed that the ER36 antagonist anordrin prevents tamoxifen-induced DISH in mice [ 46 ]. Importantly, anordrin also suppresses the growth of breast and endometrial cancer cells in vitro, suggesting that its combination with tamoxifen should not impair the antineoplastic effect of this drug on breast cancer and should also help reduce the risk of tamoxifen-induced endometrial cancer.…”
Section: Tamoxifen Corticosteroids and Anabolic Agents: If Multiple Intracellular Receptors Are Involved Just Modulate The Right One To Rmentioning
confidence: 99%
“…More recently, a similar strategy has been investigated by targeting plasma membrane ERs. More specifically, Gu et al showed that the ER36 antagonist anordrin prevents tamoxifen-induced DISH in mice [ 46 ]. Importantly, anordrin also suppresses the growth of breast and endometrial cancer cells in vitro, suggesting that its combination with tamoxifen should not impair the antineoplastic effect of this drug on breast cancer and should also help reduce the risk of tamoxifen-induced endometrial cancer.…”
Section: Tamoxifen Corticosteroids and Anabolic Agents: If Multiple Intracellular Receptors Are Involved Just Modulate The Right One To Rmentioning
confidence: 99%
“…It could play an important role in chemoprevention of breast cancer in women with high risk factors, but this still remains controversial [6]. Although the benefit of tamoxifen in the management of ER+ breast cancer has been established (low risk of recurrence and contralateral breast cancer), its risk of inducing endometrial cancer has also been recognized [7], thus raising the issue of how to counteract the tamoxifen-induced endometrial hyperplasia. Numerous authors have demonstrated that the chemopreventive effects of tamoxifen could be improved by combining it with substances that could potentiate its antitumor activity or mitigate its side effects on the endometrium [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen (TAM) is used for the treatment of breast cancer widely 3 . It is noticeable, however, that hepatocyte steatosis has been described in studies of patients with breast cancer because of TAM, 4,5 and TAM is known to induce this condition in half of the patients within the first 2 years of TAM treatment 6‐8 . Therapeutic intervention to prevent TAM‐induced hepatocyte steatosis may improve the safety of TAM usage 9 .…”
Section: Introductionmentioning
confidence: 99%